Key audit matters practices in construction sector: Evidence of Malaysian market - Ummi Junaidda, Hashim; Wan Amalina, Wan Abdullah@Wan Muda; Norsiah, Ahmad (2019)
This paper examines the reporting of Key Audit Matters (KAMs) in independent auditor's report for construction sector in the Malaysian market. It also aims to identify whether the specific characteristics of construction company will influence the KAMs reporting for Malaysian companies. The sample covers all construction companies listed on Bursa Malaysia with available data one year upon the implementation of KAMs. This business sector has been the subject of the study due to the fact that construction sector, despite being a high-risk sector, is among important sectors that contribute to the development of the economy of a country. The objective of the study is achieved through content analysis. The maximum and minimum number of KAMs disclosed are six and one respectively for this sector. The main issue addressed as KAMs in construction sector is revenue. The revenue recognition in the construction sector is affected by the unexpected occurrences and this, in turn, will affect the estimated cost and profit. The findings discover that the practice on the KAMs disclosed has been critically assessed by the auditors, but there is exception on some of the practice. In the construction sector, the items listed as KAMs basically relates to areas that required a significant amount of judgement from auditors (matters that involve high uncertainty estimation). However, for some of the KAMs disclosure, 24% of the sample do not highlight the reason of why the items listed as KAMs. This circumstance would provide questions whether auditors had dismissed the guidelines of the disclosure of KAMs or auditors did not understand the KAMs' practices comprehensively. Therefore, further monitoring is needed to ensure the successful implementation of KAMs. This study only covers a limited sample of one year upon implementation of KAMs. It provides an empirical data and description on Key audit matters (KAMs) disclosure in the independent auditor's report of the Malaysian Listed company.